Fatores de risco associados à gravidez ectópica na fertilização in vitro: estudo de caso – controle - Trindade, Vanessa Devens (2020)
Introduction: An ectopic pregnancy occurs outside the normal uterine cavity. It occurs in approximately 1.5% of the population, with an incidence 2 to 3 times higher after in vitro Fertilization treatment. The aim of this study was to evaluate the risk factors involved in the occurrence of ectopic pregnancy in patients submitted to in vitro fertilization. Methods: Case-control study using data from a reproductive medicine center in Porto Alegre - RS between 2000 and 2019. Patients were divided into two groups; group 1: 90 patients diagnosed with ectopic pregnancy and group 2: 409 patients diagnosed with intrauterine pregnancy. Student's t test, Mann Whitney U, Chisquare or Fisher's exact test were applied according to the distribution of variables. Additionally, a logistic regression model was used to assess risk factors for the occurrence of ectopic pregnancy. A significant level of α > 0.05 was adopted. Results: 2.35% of cycles with embryo transfer resulted in ectopic pregnancy during the study period. Comparing Groups 1 and 2, the following results were observed: infertility due to tubal factor was more frequent in group 1 (35.6% vs. 21.1%, p = 0.005; OR 2.0, 95% CI 1.2-3.4 , p = 0.004), as well as history of previous abortion (13.3% vs. 6.8%, p = 0.05; OR 2.0 95% CI 1.0–4.2, p = 0.044). Regarding treatment characteristics, embryo transfers in the cleavage stage (D3) were more frequent in group 1 (72.6% vs. 61.6%, p=0.04; OR 1.9 CI 95% 1.0 - 3.3, p = 0.025) and, also, transfer of two or more embryos (89.6% vs. 80.9%, p=0,03; OR 2.5 CI 95% 1.1–5.7, p = 0.025). After adjusting for maternal age, year of treatment and number of mature oocytes, statistical significance was maintained, except for a previous history of abortion. There were no differences in the other factors analyzed. We separately analyzed oocyte recipient cycles, as they had been excluded from the previous analysis. The incidence of oocyte recipient patients was higher in group 1 (10% (10/100) vs. 3.1% (13/422), p = 0.005, OR 3.4 95% CI 1.48 - 8.22 p = 0.004). Conclusion: History of tubal factor infertility, transfer of cleavage stage embryos, as well as transfer of more than one embryo were all associated with higher ectopic pregnancy risk. Previous miscarriage history, after adjusting for confounding factors, did not appear as a risk factor for ectopic pregnancy, but it seems to have a clinical relevance and should be considered. Finally, oocyte recipient patients seem to have a greater chance of developing an ectopic pregnancy, a finding that should be carefully analyzed, given the sample size of the study.